Perception of Doctors towards Relationship with Pharmaceutical Industry - Mumtaz Ahmad, Neelam Zaka, Inayat ur Rahman, Sehrish Mumtaz, Mobina Ahsan Dodhy, Mumtaz Ahmad, Neelam Zaka, Inayat ur Rahman, Sehrish Mumtaz, Mobina Ahsan Dodhy; Lubna Meraj, Lubna Meraj (Journal of Rawalpindi Medical College, 2022)
Doctors and the pharmaceutical companies are the main component of health care system which is also essential for each other. Their interdependency on such a large scale calls for a better relationship between these two stakeholders of the health care system. But most of the time this relationship is used in a negative way which not only has a bad impact on the reputation of this prestigious medical profession but also affects the health of the patient which are the ones to bear the effects of this malafied relationship. In order to see how this relationship works in the hospitals of Azad Kashmir, this study was conducted on the doctors of Abbas Institute of Medical Sciences, Muzaffarabad. Due to shortage of time and limited resources only one hospital was selected for the study to be carried out. This was a mixed study carried out from January through June 2017. In our study 100 doctors were selected for data collection in questionnaire method. While three different focus groups involving doctors from different specialties were made. Out of 100 doctors, 36 doctors agreed that the doctors in AIMS are aware of such guidelines, 92 doctors agreed that there is need of national guidelines to monitor the doctor and pharmaceutical company’s relationship, 67 responded that doctor’s prescription is influenced by the gifts given by pharmaceutical companies, 52 doctors agreed that pharmaceutical companies should be banned from giving gifts to physicians, 88 responded that the information provided by those representatives is only superficial and they don’t know the core information like side effects and mode of action of the drugs, 15 thought that yes it is ethical to accept the gifts from the pharmaceutical companies but only to the extent of samples of medicines and out of 100, 89 doctors responded in favor of incorporation of bioethics in the curriculum of the medical education. During focus group discussion on the topic, three themes which were finalized after detailed deliberation and these themes were, Doctor-Pharma Regulations, Accepting the gifts from Pharmaceutical Companies and influence of these Interactions on Physicians’ drug prescribing Behaviors and how the prescribing behaviors of doctors. Conclusion: It is concluded that pharmaceutical companies have hijacked our whole health system to some extent and our whole health system is polluted because of these Pharmaceutical company’s representatives and there is a need to ascertain the fact that if this phenomenon is not controlled, in near future we will have to face very severe consequences and our patients will be at the mercy of pharmaceutical companies rather than the doctor.